MENUMBUHKAN JIWA WIRAUSAHA KAWULA MUDADI ERA MILENIAL MELALUI PENDEKATAN INSIDE-OUT - Yuliani, Nafisah; Novita, Diana; Pramestari, Diah (IKRA-ITH ABDIMAS, 2019)
ABSTRAKThe potential for development and development of an entrepreneurial spirit in theyounger generation is still not optimal. This is because the level of education of mostaudiences is high school (SMA) who have never received debriefing about entrepreneurship.The aim of community service is to see the students abilities for themselves through selfconcept,entrepreneurial interest, entrepreneurial traits, own skills, abilities and backgroundthat determine what type of business will be pioneered. Then there needs to be an effort tofoster an entrepreneurial spirit through an inside-out approach. Inside-out approach. TheInside-out approach means initiating something (including making changes) from yourself,not from outside parties. The variables used are self-concept, entrepreneurial interest andentrepreneurial characteristics. Data were obtained through pretest and post testquestionnaires distributed to students. The results show Pretest is done on the variables ofself-concept, entrepreneurial interest and entrepreneurial characteristics. The results ofpretest-variable business interests showed an average of 65.08%. Based on scoreinterpretation criteria, it can be concluded that students self-concept towardsentrepreneurship is strong. The pretestminate results of entrepreneurship show an average of90.08%. Based on the score interpretation criteria, it was concluded that studentsentrepreneurial interest in entrepreneurship was very strong. Post test results onentrepreneurship shows an average of 91.52%. Based on the score interpretation criteria, itwas concluded that students entrepreneurial interest in entrepreneurship was very strong. Theresults of the pre test entrepreneurial characteristics show that the average of Nikai is 77.26%.The post test results showed an average value of 77.78%. Based on the interpretation criteriathe score is concluded that the characteristics of students entrepreneurship towardsentrepreneurs are strong. The results of the post test did not show results that were notsignificantly different from the results of the pre-test. The inside-out approach is a reflectionof the attitude of proactivity, which is to make oneself as a person who is empowered (at thesame time responsible) in creating a positive influence on the surrounding environment. Thisinside-out approach is very good in developing students personally to become independententrepreneurs in the future.